2007
DOI: 10.1175/jhm575.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Projection of Arctic Freshwater Budget Components by the IPCC AR4 Global Climate Models

Abstract: The state-of-the-art AOGCM simulations have recently (late 2004-early 2005) been completed for the Intergovernmental Panel on Climate Change (IPCC) in order to provide input to the IPCC's Fourth Assessment Report (AR4). The present paper synthesizes the new simulations of both the twentieth-and twenty-first-century arctic freshwater budget components for use in the IPCC AR4, and attempts to determine whether demonstrable progress has been achieved since the late 1990s. Precipitation and its difference with ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
111
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 23 publications
11
111
0
2
Order By: Relevance
“…The AR4 models have also revised the aggregate projections for the major basins in the pan-Arctic drainage basin, pointing overall to somewhat lower increases in temperature and precipitation than previously anticipated for the early twenty-first century, and to a considerably lower increase by the end of the century. In an analysis of modeled precipitation for the twentieth century control runs, Kattsov et al (2007) found a similar change toward lower precipitation values for the AR4 ensemble. This is most likely due to changes in the model representation of precipitation (Kattsov et al 2007), but effects of outlier models may also have influenced TAR results more strongly than the AR4 average results, which are based on more models.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The AR4 models have also revised the aggregate projections for the major basins in the pan-Arctic drainage basin, pointing overall to somewhat lower increases in temperature and precipitation than previously anticipated for the early twenty-first century, and to a considerably lower increase by the end of the century. In an analysis of modeled precipitation for the twentieth century control runs, Kattsov et al (2007) found a similar change toward lower precipitation values for the AR4 ensemble. This is most likely due to changes in the model representation of precipitation (Kattsov et al 2007), but effects of outlier models may also have influenced TAR results more strongly than the AR4 average results, which are based on more models.…”
Section: Discussionmentioning
confidence: 78%
“…In an analysis of modeled precipitation for the twentieth century control runs, Kattsov et al (2007) found a similar change toward lower precipitation values for the AR4 ensemble. This is most likely due to changes in the model representation of precipitation (Kattsov et al 2007), but effects of outlier models may also have influenced TAR results more strongly than the AR4 average results, which are based on more models.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Annual precipitation in the Arctic is projected to increase by 20% by the end of the twenty-36 first century (ACIA, 2004), among the highest globally, and this is a consistent feature among 37 state-of-the-art global climate models (Kattsov et al, 2007). The anticipated climate changes, 38 and especially those related to hydrology, will have a large impact on sources and sinks of 39 greenhouse gases related to the Arctic tundra (Jørgensen et al, 2015), on local societies in the 40 Arctic, and will likely impact lower latitudes through climatic teleconnections (Førland et al,41 2009).…”
mentioning
confidence: 98%